Feasibility, acceptability, and preliminary impact of an mHealth supported breastfeeding peer counselor intervention in rural India. Issue 1 (20th February 2021) - Short, Vanessa L.; Bellad, Roopa M.; Kelly, Patricia J.; Washio, Yukiko; Ma, Tony; Chang, Katie; Majantashetti, Niranjana S.; Charantimath, Umesh S.; Jaeger, Frances J.; Lalakia, Parth; Goudar, Shivaprasad S.; Derman, Richard
Abstract: Objective: To evaluate the feasibility of an mHealth‐supported breastfeeding peer counselor intervention implemented in rural India and the preliminary impact of the intervention on maternal breastfeeding behaviors, including exclusive breastfeeding (EBF). Methods: In this quasi‐experimental pilot study, participants received either the intervention plus usual care ( n = 110) or usual care alone ( n = 112). The intervention group received nine in‐home visits during and after pregnancy from peer counselors who provided education about and support for EBF and other optimal infant feeding practices and were aided with an mHealth tool. The control group received routine prenatal and postnatal health education. Progress notes and surveys were used to assess feasibility. Logistic regression models were used for between‐group comparisons of optimal infant feeding outcomes, including EBF for 6 months. Results: The intervention was delivered as intended, maintained over the study period, and had high acceptability ratings. There were statistically significant differences in all outcomes between groups. The intervention group had a significantly higher likelihood of EBF at 6 months compared to the control group (adjusted odds ratio 3.57, 95% confidence interval 1.80–7.07). Conclusion: Integration of mHealth with community‐based peer counselors to educate women about EBF is feasible and acceptable in rural India and impacts maternal breastfeeding behaviors. Synopsis: Integration of mHealth with community‐based peer counselors to educate women about exclusive breastfeeding is feasible and acceptable in rural India and impacts maternal breastfeeding behaviors.